2013
DOI: 10.1016/j.mambio.2012.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anthropic pressures and elevation on the large and medium-sized terrestrial mammals of the subtropical mountain forests (Yungas) of NW Argentina

Abstract: a b s t r a c tWe conducted a 55-day long camera-trap survey in the Yungas subtropical forest in NW Argentina, to assess the effect of human accessibility, conservation status of the area, domestic animals and elevation on the diversity and composition of the large and medium-sized native terrestrial mammal assemblage. We deployed 24 camera-trap stations at distances of ∼2 km from each other. The study area is covered by continuous forest and has its center in the small community of Acambuco, in the Acambuco P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…As predicted, elevation was also influential covariate for ocelot habitat use. Previous studies indicated that the probability of habitat use by ocelots decreased with elevation (Ahumada, Hurtado, & Lizcano, ; Di Bitetti, Albanesi, Foguet, De Angelo, & Brown, ). Perhaps this is because lowland forests have higher net primary productivity (Robertson et al., ), which may increase resources (Peres, ) to sustain a greater abundance of ocelot prey.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As predicted, elevation was also influential covariate for ocelot habitat use. Previous studies indicated that the probability of habitat use by ocelots decreased with elevation (Ahumada, Hurtado, & Lizcano, ; Di Bitetti, Albanesi, Foguet, De Angelo, & Brown, ). Perhaps this is because lowland forests have higher net primary productivity (Robertson et al., ), which may increase resources (Peres, ) to sustain a greater abundance of ocelot prey.…”
Section: Discussionmentioning
confidence: 91%
“…Estimates and standard error (SE) of untransformed covariate effects (β parameters) are given for the most parsimonious model that included the covariate. (Ahumada, Hurtado, & Lizcano, 2013;Di Bitetti, Albanesi, Foguet, De Angelo, & Brown, 2013). Perhaps this is because lowland forests have higher net primary productivity (Robertson et al, 2010), which may increase resources (Peres, 1994) to sustain a greater abundance of ocelot prey.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the distribution of mammal diversity on mountains has until now focused on small mammals (mostly on Insectivora, Rodentia with body weights of 2 g–5 kg), which nearly exclusively show unimodal distributions of elevational diversity (e.g. Brown, ; McCain, ; but see Di Bitetti, Albanesi, Foguet, De Angelo, & Brown, ; Ferreira de Pinho, Braga Ferreira, & Pereira Paglia, ). In contrast, research on large mammals along altitudinal gradients has been scarce.…”
Section: Introductionmentioning
confidence: 99%
“…We expect species richness and community biomass of wild mammals to be higher in protected than in unprotected areas. Additionally, we expect that the species richness of mammals decreases with increasing land‐use intensity and with the occurrence of domestic mammals (Di Bitetti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…En los Andes argentinos las especies de mamíferos pequeños no nativos tienen un mayor éxito en zonas perturbadas, desplazando o reemplazando a las especies nativas locales (Martin-Albarracin et al 2015). Así, los resultados sugieren que los pequeños mamíferos son sensibles a la presencia humana y sus actividades, como ha sido reportado en otras localidades (Olifiers et al 2005, Di Bitetti et al 2013. Además, la presencia de especies exóticas como ratas, ratones, perros y gatos probablemente está afectando la fauna local vía depredación, transmisión de enfermedades o competencia (Dabritz et al 2006, Calver et al 2011Sierra et al 2011).…”
Section: Discussionunclassified